COLONIZATION OF PATHOGENIC AEROBIC BACTERIA IN THE EXTERNAL EAR AND EFFECTS OF CERUMEN TYPES, AGE, AND GENDER ON COLONIZATION - Al-Khamesy, Khaled Saad Abdulrahman; Al-Moyed, Khaled Abdul-Karim A; Al-Shamahy, Hassan Abdulwahab (Universal Journal of Pharmaceutical Research, 2023)
Aims: The study aimed to study the prevalence of pathogenic aerobic bacteria colonization in the outer ear and to determine the prevalence of cerumen types among different ages and sex of selected individuals in Sana'a city. Also determined the effects of cerumen types, age, and gender on the incidence of pathogenic aerobic bacterial colonization. Methods: The present study was take place in the Department of Medical Microbiology and ENT Department, Faculty of Medicine and Health Sciences, Sana’a University. The study request was acceptable by the ethics committee of the Faculty. Written informed consent was taken from the chosen participants. Families of the study sample members residing in the various sectors of Sana'a city were visited at home in which participants were randomly selected from all age groups and sexes. Households were reviewed on time and clinical examination of the ear was done and results were recorded and ear swab samples were collected. The rapid visual identification of cerumen was performed. The culture samples were collected and transferred to the laboratory then culture and bacterial growth was identified by standard bacteriological methods. Results: The study included 246 healthy persons, 33.3% of them male and 66.7% were females. The age ranged from 1 -80 years with mean age equal to 34.2±18.7 years, 96.3% of the study subjects have the wet type and only 3.7% have the dry type of cerumen, 2.03% had impacted cerumen. The most prevalent isolate from the outer ear was Staphylococcus aureus with 35 strains (14.2%), followed by Psedumonas aureginosa with 14 strains (5.7%). Klebsiella spp, Streptococcus pyogenes and Hemophilus influenzae isolates were less frequent with 7 (2.8%), 6 (2.4%) and 5 (2.03%) isolates, respectively. Positive growth for bacterial pathogens was significantly associated with males (OR=1.8, p=0.03), ≤15 years group (OR=2.5, p=0.01), and dry-type cerumen (OR=8.9, p=0.001). Conclusion: There are two distinct and specific types of cerumen, wet and dry, of which the wet type appears to be the most common in Yemen, and of the subspecies of the wet type, honey brown was dominant. The present study concluded that some pathogenic bacteria that can cause otitis externa are naturally present in the normal external auditory canal. The most prevalent isolate was Staphylococcus aureus, followed by Psedumonas aureginosa, Klebsiella spp, Streptococcus pyogenes, and Hemophilus influenzae. Hence clinicians must find a history of any predisposing factors before interpreting laboratory culture reports. Peer Review History: Received: 1 October 2022; Revised: 8 November; Accepted: 12 December 2022, Available online: 15 January 2023 Academic Editor: Dr. Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewers: Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com Dr. A.A. Mgbahurike, University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com